2021
DOI: 10.48550/arxiv.2107.06834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On The Spin Dynamics of Elongated Minor Bodies with Applications to a Possible Solar System Analogue Composition for `Oumuamua

Darryl Seligman,
W. Garrett Levine,
Samuel H. C. Cabot
et al.

Abstract: The first interstellar object, 1I/2017 U1 ('Oumuamua), exhibited several unique properties, including an extreme aspect ratio, a lack of typical cometary volatiles, and a deviation from a Keplerian trajectory. Several authors have hypothesized that the non-gravitational acceleration was caused by either cometary outgassing or radiation pressure. Here, we investigate the spin dynamics of 'Oumuamua under the action of high surface area fractional activity and radiation pressure. We demonstrate that a series of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The mechanical stability of these dust aggregates subjected to tidal torques around perihelion was demonstrated by Flekkøy et al (2019). Furthermore, Seligman et al (2021) demonstrated that the spin-state and thus, the lightcurve, of objects driven by solar radiation pressure is stable. Moreover, the creation of extremelyporous aggregates would not deplete the mass reservoir of rocky and icy material in extrasolar systems.…”
Section: Ultra-porous Dust Aggregatesmentioning
confidence: 96%
See 2 more Smart Citations
“…The mechanical stability of these dust aggregates subjected to tidal torques around perihelion was demonstrated by Flekkøy et al (2019). Furthermore, Seligman et al (2021) demonstrated that the spin-state and thus, the lightcurve, of objects driven by solar radiation pressure is stable. Moreover, the creation of extremelyporous aggregates would not deplete the mass reservoir of rocky and icy material in extrasolar systems.…”
Section: Ultra-porous Dust Aggregatesmentioning
confidence: 96%
“…6.2. A Solar System Small Body Analogue Seligman et al (2021) showed that carbon monoxide (CO) outgassing could reconcile the energetics of the non-gravitational acceleration with outgassing. While this solar system volatile could place the ISO within known realms of small bodies, the Spitzer non-detection places strict limits on cometary activity from this substance during the observational window.…”
Section: Ultra-porous Dust Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is distinctively rich in CO relative to Solar System comets (Bodewits et al 2020;Cordiner et al 2020). Seligman et al (2021) argue that both of these interstellar objects can be plausibly considered as COenriched planetesimals -if 1I had variable activity, a common state for comets.…”
Section: Comparison With Observed Isosmentioning
confidence: 96%
“…The non-gravitational acceleration has been postulated to be driven by radiation pressure (Micheli et al 2018), which could be explained if 'Oumuamua was an ultra low-density fractal aggregate (Moro-Martín 2019; Luu et al 2020;Sekanina 2019), or a millimeter-thin artificial light sail (Bialy & Loeb 2018). If the non-gravitational acceleration was powered by cometary outgassing (Micheli et al 2018;Seligman et al 2019), it has been demonstrated that the energetics are consistent with the sublimation of H 2 (Füglistaler & Pfenniger 2015;Seligman & Laughlin 2020;, N 2 , or CO (Seligman et al 2021).…”
Section: Introductionmentioning
confidence: 99%